IMPACTOS AMBIENTAIS NO PROCESSO DE OCUPAÇÃO DO BAIRRO COROA DO MEIO, EM ARACAJU/SERGIPE - Vasconcelos, Luciano; Santos, Débora; Farias, Ana Maria (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Civil construction is one of the activities that most impacts society, generating benefits or drawbacks. This industry has direct influence in the environmental, social, economical and visual of a city or area, and it responds by negative impacts of anthropogenic actions. The objective of this research was to point out the main environmental impacts caused by the urban occupation and the formation of the District Coroa do Meio, Aracaju/Sergipe, during the period of 1976 to 2017. The methodological procedures used bibliographical, historical and geographical research in a case study. For this, it was used maps or satellite images of the area in the years 1976, 1978, 1984, 2003, 2008, 2010, 2013. These informations were put in the Quantum Gis software 2.14.3®, adopting as the method the Overlay mapping and analysis of the superposition of maps between the years mentioned. The information obtained to assist in the interpretation of the impact of construction on the process of occupation of the area through Visual information and interference in the land use, from a multitemporal analysis, enabling the creation of an inventory about of the studied area.